Cut to the chase 100 matrix pearls for doctors - Gordon, Leo A. (Tfm Pub., 2006)
Matrix pearls are the glue that holds medicine together. They are the valuable kernels of wisdom and experience that guide physicians through the complexities of modern medical practice. This book takes the grand oral traditions of medicine and records them as useful lessons.